Methods for Extraction of Muscle Proteins from Meat and Fish Using Denaturing and Nondenaturing Solutions - Antonella della Malva; Marzia Albenzio; Antonella Santillo; Donatella Russo; Lucia Figliola; Mariangela Caroprese; Rosaria Marino (Journal of Food Quality)
The objective of the present study was to test two extraction methods including solutions with different ionic strengths on the extraction and separation of the myofibrillar proteins from meat and fish muscles of different species. Meat samples from longissimus thoracis muscle of beef and lamb, pectoralis major muscle of chicken, and dorsal white muscle of fish from sole (Solea solea), European hake (Merluccius merluccius), and sea bass (Dicentrarchus labrax) were analyzed. The extraction method using nondenaturing solution led to a major extraction of high molecular-weight proteins as myosin heavy chain, α-actinin, and desmin; on the contrary, the denaturing method provided a good protein extractability of proteins and fragments with low molecular-weight as actin, troponin-T, tropomyosin, and myosin light chain 1 and 2 proteins for the most meat and fish samples. The nondenaturing extraction method showed several advantages resulting in time and labour saving and in minimizing the use of toxic and polluting agents.